Study on The Technical Plan of Continuous Beam Rotation Construction Monitoring and Early Warning. Issue 2 (July 2021) - Wu, Sitong; Qian, Jin
Abstract: The rotating construction of the bridge is the better choice, the continuous beam rotation intelligent monitoring system was built by the Academy of Railway Sciences and was developed and applied based on the "Smart Construction Site" project of the Huzhou-Hangzhou Railway. Firstly, this article introduces the system. The system is based on Beidou's high-precision satellite positioning solution system to calculate the attitude of the bridge during the construction of the rotating body. The key stress level and change of the bridge can be obtained through the stress sensor, which can obtain the response trend of the pontic structure, and effectively control the stress damage and dangerous points in the first time. Secondly, it continuously moitors the temperature and humidity of the rotating bridge, wind speed, bridge pier strain, inclination angle, and rotation angle in real time during the entire course of the bridge rotation to ensure the safety of construction. Thirdly, points out the location of the sensor buried in the foundation pit during the bridge construction process. Finally, the principle and composition of the bridge health warning technology scheme based on BIM technology are introduced, and its significance and advantages are summarized. Provides solutions and experience for the long-term monitoring of bridges in rotating construction.